Gender-based violence in higher education institutions in Ecuador: a systematic literature review - Laz-Figueroa, Kenia; Guevara-Viejó, Fabricio; Valenzuela-Cobos, Juan Diego; Hernández-Sánchez, Brizeida Raquel; Sánchez-García, José Carlos (Frontiers in Education, 2026)
Gender-based violence in Ecuador’s higher education institutions (HEIs) is a structural and widespread problem, rooted in patriarchal sociocultural norms. It mainly affects women and gender-based groups, manifesting itself as sexual harassment, psychological violence, and discrimination. The objective of this research is to synthesize the existing literature on the causes, manifestations, and institutional responses to gender-based violence in Ecuadorian HEIs, in order to categorize the types of violence, evaluate protocols, and propose actions based on international best practices. The methodology developed was a systematic review of qualitative literature in databases such as Scopus and SciELO (2019–2025), using keywords related to gender-based violence in universities. Of the 234 initial articles, 23 were selected that met criteria of relevance and methodological rigor. The analysis focused on categorizing types of violence, risk factors, and institutional responses. The studies reveal that gender-based violence in HEIs is frequent but underreported due to cultural normalization and mistrust of protocols. Sexual harassment and psychological violence stand out, with victims mainly being women and LGBTIQ+ people. Although regulations exist, their implementation is poor, with a lack of dissemination and training. The research concludes that eradicating gender-based violence in HEIs requires comprehensive policies, gender-sensitive education, and accessible reporting mechanisms. Sustained institutional commitment and active participation by the university community are essential to transform patriarchal structures and ensure safe and inclusive environments.